Beyond conventional therapies - an overview of the alternative approaches in migraine management - Barg, Marta; Biały-Karbowniczek, Julia; Jędrasek, Aleksandra; Wojtyła, Klaudia (Journal of Education, Health and Sport, 2024)
Introduction: Migraine remains one of the most prevalent chronic neurological conditions that significantly impacts the quality of life. The treatment aims to help with the symptoms and prevent further attacks. There are several pharmacological methods, but because of their side effects, sometimes lower-than-expected effectiveness, costs, and long-term dependency, non-pharmacological approaches have gained popularity. Review methods: We conducted our study as a literature review, with data gathered via PubMed and Embase. The state of knowledge: Managing migraine is hard to achieve based only on pharmacological therapy. Recently, the development of alternative approaches, such as cognitive behavioral therapy, acupuncture, or butterbur, has been observed. Many studies try to assess its effectiveness. Biofeedback is a promising treatment method, however, it is expensive and requires special equipment. Aerobic training is essential in the prevention and therapy of many illnesses and proper intensity can be helpful with migraines, while yoga is a great lower-intensity option. Conclusions: Alternative methods may be a great alternative or support in migraine management. However, there is still a need for standardized investigations to evaluate effectiveness and safety.